2018
DOI: 10.3382/ps/pex377
|View full text |Cite
|
Sign up to set email alerts
|

Application of Paracoccus marcusii as a potential feed additive for laying hens

Abstract: Carotenoids have been used for many years as an added pigment to enhance egg yolk color. One such carotenoid, astaxanthin, has a strong antioxidant activity and is produced by several microorganisms, including the bacterium Paracoccus marcusii, which has shown promise to be used as a feed additive. Therefore, this study investigated the use of P. marcusii as a possible source of pigmentation in layer hen feed to enhance egg yolk color. Paracoccus marcusii was fed to hens in a sucrose solution (10% m/v). The he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…(2021) reported that Ax addition had no effect on egg weight and egg mass, but feed intake tended to increase. Compared to the white-corn based diet, Paracoccus marcusii -sourced Ax increased egg production, but did not influence the body weight of hens ( Conradie et al., 2018 ). Marine byproducts, including scallop viscera, squid viscera, and shrimp head, added at 50 g/kg as dietary Ax sources affected egg laying rate, egg mass, and feed conversion ratio.…”
Section: Application Of Astaxanthin In Laying Hensmentioning
confidence: 97%
See 2 more Smart Citations
“…(2021) reported that Ax addition had no effect on egg weight and egg mass, but feed intake tended to increase. Compared to the white-corn based diet, Paracoccus marcusii -sourced Ax increased egg production, but did not influence the body weight of hens ( Conradie et al., 2018 ). Marine byproducts, including scallop viscera, squid viscera, and shrimp head, added at 50 g/kg as dietary Ax sources affected egg laying rate, egg mass, and feed conversion ratio.…”
Section: Application Of Astaxanthin In Laying Hensmentioning
confidence: 97%
“…The quality of the albumen and physical indices do not appear to be sensitive to dietary Ax. Most literature showed that albumen height, Haugh unit, eggshell thickness, and eggshell strength were unaffected by dietary Ax in laying hens ( Conradie et al., 2018 ; Dansou et al., 2021 ; Heng et al., 2021 ; Honda et al., 2021 ). Only a few studies fortuitously found that dietary Ax increased eggshell weight ( Zhu et al., 2021 ) and egg size ( Conradie et al., 2018 ).…”
Section: Application Of Astaxanthin In Laying Hensmentioning
confidence: 99%
See 1 more Smart Citation
“…Paracoccus is a diverse genus in which Paracoccus marcusii, like the Dietzia sp. discussed above, produces carotenoids studied for utilization as a source of pigmentation in layer hen feed to enhance egg yolk color [56,57]. Paracoccus denitrificans is studied industrially for its nitrate reducing capabilities and can cause the degradation of nitrogen additives used to fertilize crop soils.…”
Section: Spent Beetle: Alpha Diversitymentioning
confidence: 99%
“…Currently, canola meal (CM) has been proposed as an alternative source of protein (Min et al 2011;Wickramasuriya et al 2015). There have been trials evaluating the use of CM as a substitute for soybean meal in broiler diets, but an appropriate number of enzymes must be added to improve feed digestion in chicken industry (Irani et al 2012;Conradie et al 2018). Canola had great potential as an alternative replacement to soybean meal in broiler diets and could be helpful in designing low-cost feed formulations that would improve growth performance and health status in poultry farming systems in the future (Disetlhe et al 2018).…”
Section: Introductionmentioning
confidence: 99%